2016
DOI: 10.1016/j.jtcvs.2016.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Resection of a posterior mediastinal mass: Lessons learned from a failed exploration for presumed schwannoma

Abstract: Side-by-side comparison of thoracic chordoma versus extradural schwannoma. Central MessageMisdiagnosis and pitfalls in the operation for posterior mediastinal mass can be avoided with a multidisciplinary team approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…But, as previously reported, a mediastinal mass is not always what it seems and can create some surprises during surgical resection. 9 This was the case in our patient when we discovered a cardiac tumor arising from the epicardium.…”
Section: Discussionmentioning
confidence: 59%
“…But, as previously reported, a mediastinal mass is not always what it seems and can create some surprises during surgical resection. 9 This was the case in our patient when we discovered a cardiac tumor arising from the epicardium.…”
Section: Discussionmentioning
confidence: 59%
“…A biopsy was successfully completed and revealed that the tumour was actually a chordoma. On CT, the mass showed obliteration of the plane between the spine and tumour, more characteristic of a chordoma [ 8 ]. This case highlights the importance of chordomas in the differential diagnosis, despite their rarity.…”
Section: Discussionmentioning
confidence: 99%
“…It was mentioned that the most common presenting complaint was chest or back pain, followed by anterior mediastinal compression syndrome, hoarseness, dysphagia, and cough. 5 One-third of reported patients were asymptomatic and detected during routine chest examinations 20 Many preliminary reports described several presentations for thoracic chordoma 10 , 12 , 15 Among these reports, chordomas were initially misdiagnosed as different neoplasia, including hemangioma, benign neurinomas, 23 and adenocarcinomas. 13 Others reported chordomas metastasizing to lymph nodes, lungs, 18 bones, brain, and viscera.…”
Section: Discussionmentioning
confidence: 99%